MANAJEMEN PROGRAM INTENSIF BAHASA ARAB PADA PEMINATAN KEAGAMAAN MAN 2 KOTA MALANG - M. Rozy Zamroni; A'yunin Aditya Fajrin; Tabassum Aliyatuz Zahroh; Nur Kholid (Idaarah: Jurnal Manajemen Pendidikan, 2023)
The purpose of this research is to determine the planning and actuating of management in the intensive Arabic program for religion specialization as the MAN-PK stub of MAN 2 Kota Malang and to analyze the supporting factors and obstacles found in the process while running the program. The method used in this research is a qualitative method. The data obtained by observation and interviews were then analyzed descriptively. The results of this study are; (1) planning management program is carried out properly in accordance with the objectives of the program; (2) supporting teachers used strategies that accordance with planning and objectives in implementing the program; (3) the majority of students have the same orientation even though some students think to change their specialization is one of the obstacles in this intensive Arabic language program.